Could cholecystectomy be abandoned after removal of bile duct stones by endoscopic retrograde cholangio-pancreaticography? - (:unkn) unknown (ELSEVIER SINGAPORE PTE LTD, 2021)
Background/objective: The current treatment for choledocholithiasis is endoscopic common bile duct clearance followed by cholecystectomy. However, few studies have investigated whether cholecystectomy is necessary after the endoscopic removal of bile duct stones. This study aimed to determine the rate of patients without symptoms during the follow-up period after endoscopic retrograde cholangiopancreaticography (ERCP). Materials and methods: We retrospectively analyzed data from patients with choledocholithiasis who underwent ERCP from a single centre.The patients were invited to the hospital for evaluation of symptoms during the follow-up period after ERCP. The primary outcome of this study was to determine the rate of patients with symptoms during the follow-up period after ERCP. Results: A total of 286 patients with a median age of 57 (18-95) years old were included in the study. Of these, 195patients (68%) remained asymptomatic during the follow-up period of 18 months (1-70) after endoscopic sphincterotomy without cholecystectomy. A total of 75(50%) out of 151 patients who underwent cholecystectomy reported having symptoms after ERCP. In contrast, 119 (88%) out of 135 patients did not undergo cholecystectomy after the ERCP, remained asymptomatic during a median follow-up period of 43 months (11-70). The estimated 5-year asymptomatic rates of the patients after ERCP were 51% for the whole cohort (n = 286) according to Kaplan-Meier analysis. Conclusion: Majority of patients with choledocholithiasis who did not undergo cholecystectomy after ERCP were asymptomatic during the follow-up period. Thus, cholecystectomy may be unnecessary after endoscopic sphincterotomy for bile duct stones within a midterm period. (C) 2021 Asian Surgical Association and Taiwan Robotic Surgery Association. Publishing services by Elsevier B.V.
Keywords: Common bile duct stone; Endoscopic sphincterotomy; Cholecystectomy; GALLBLADDER IN-SITU; LAPAROSCOPIC CHOLECYSTECTOMY; SPHINCTEROTOMY; MANAGEMENT; CALCULI